Performance of beginning teachers in the licensure examination for teachers: a national study - Abao, Ethel L.; Petancio, Jo Ann M.; Sanchez, Joje Mar P.; Sumalinog, Gino G. (Frontiers in Education, 2023)
The study explored the performances of teacher education graduates in the licensure examination for teachers (LET). The descriptive-comparative research was conducted through a survey questionnaire administered online to 2,780 beginning teachers across the 16 regions in the Philippines. The findings of this study revealed that the graduates in Elementary Education (BEEd) and Secondary Education (BSEd) had satisfactory LET performances from 2017 to 2019. The comparative analysis found that these LET performances significantly vary in their examination year, degree program, specializations, examination components, locale, and type of higher education institution. Furthermore, the performance of graduates in the LET examination could be attributed to their test-taking time, college preparation, and grade point average. Hence, the graduates' satisfactory performances and significant impact on college preparation show that teacher education institutions have aligned their offerings to the standards set by the country'sThis is a provisional file, not the final typeset article higher education and licensure system. Strengthening curricular enhancement programs, reinforcing constructive alignment, and intensifying retention policy and mentoring practices were recommended.